Microstructure characterization of Al/Calcined Dolomite Metal Matrix Composites - Banjuraizah, Johar; Azlin Fazlina, Osman; Alina Rahayu, Mohamed; N.A. Rejab; N.K. Su; M.S. Talib (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.